Diversity of SHV and TEM β-Lactamases in Klebsiella pneumoniae: Gene Evolution in Northern Taiwan and Two Novel β-Lactamases, SHV-25 and SHV-26 - Chang, Feng-Yee (American Society for Microbiology, 2001)
A total of 113 blood culture isolates of Klebsiella pneumoniae from 10 hospitals in northern Taiwan were studied for SHV and TEM β-lactamase production. bla(SHV) was amplified from all isolates by PCR. TEM-type resistance, was found in 32 of the isolates and was of the TEM-1 type in all isolates. SHV-1, -2, -5, -11, and -12 and two novel enzymes were identified. These novel enzymes were designated SHV-25 and SHV-26 and had pIs of 7.5 and 7.6, respectively. Amino acid differences in comparison to the amino acid sequence of bla(SHV-1) were found at positions T18A (ThrACC→AlaGCC), L35Q (LeuCTA→GluCAA), and M129V (MetATG→ValGTG) for SHV-25 and at position A187T (AlaGCC→ThrACC) for SHV-26. The results of substrate profiles and MIC determinations showed that the novel enzymes did not hydrolyze extended-spectrum cephalosporins, rendering the isolates susceptible to these agents. Inhibition profiles revealed that the 50% inhibitory concentration for SHV-26 was higher than those for SHV-1 and SHV-25, resulting in an intermediate resistance to amoxicillin-clavulanic acid. Forty-nine ribotypes were identified, suggesting that major clonal spread had not occurred in any of the hospitals. According to the amino acid sequence, SHV β-lactamases in Taiwan may basically be derived through stepwise mutation from SHV-1 or SHV-11 and further subdivided by four routes. The stepwise mutations initiated from SHV-1 or SHV-11 to SHV-2, SHV-5, and SHV-12 comprise the evolutionary change responsible for extended-spectrum β-lactamase (ESBL) production in Taiwan. The stepwise mutations that lead to a non-ESBL (SHV-25) and the β-lactamase (SHV-26) with reduced susceptibility to clavulanic acid are possibly derived from SHV-11 and SHV-1, respectively. The results suggest a stepwise evolution of SHV β-lactamases in Taiwan.